Narrative Hermeneutics as Digital Tafsīr: Reconstructing Qur’anic Meaning and Religious Authority on Instagram @NadirsyahHosen_Official - Salma, Yusrina; Zahrotul Kamilah; Zaidanil Kamil, Ahmad; Fejrian Yazdajird Iwanebel; Muhamad Irfan Maulana (Jurnal Lektur Keagamaan, 2025)
This study examines emerging trends in digital Qur’anic interpret-tation by analyzing how Nadirsyah Hosen employs narrative hermeneutics on his Instagram account @nadirsyahhosen_official. Existing research on digital tafsīr has largely focused on thematic content, presentation style, or audience interaction, yet little attention has been given to the use of storytelling as an interpretive method. This study fills that gap by investi¬gating how narrative structures function as hermeneutic tools in interpret¬ting Sūrah al-Falaq and al-Nās. The research employed a qualitative design that integrates two forms of data: Instagram posts containing Hosen’s story-based interpretations and user comments responding to these posts. Narrative analysis based on Labov and Waletzky’s framework is applied to identify the structural components of the stories, while netnographic analysis is used to examine audience reception patterns. The findings show that Hosen’s interpretations consistently incorporate key narrative elements such as orientation, complication, evaluation, resolution, and coda, which enhance communicative clarity and contextual relevance. Audience res¬pon¬ses cluster into four dimensions: emotional spiritual engagement, epis¬te¬mic trust in religious authority, social communitarian bonding, and educational pragmatic learning. These results demonstrate that narrative hermeneutics strengthens interpretive authority and fosters participatory religious discourse in digital environments. The study concludes that storytelling functions not only as a rhetorical device but also as an epistemic strategy that reshapes Qur’anic interpretation in the digital age. It recommends further exploration of narrative based tafsīr across diverse platforms and audiences.